Rh(I)(2,5-norbornadiene)(biphenyl)(tris(4-fluorophenyl)phosphine): Synthesis, Characterization, and Application as an Initiator in the Stereoregular (Co)Polymerization of Phenylacetylenes - Loong Tan, N.S.; Nealon, G.L.; Turner, G.F.; Moggach, S.A.; Ogden, Mark; Massi, Max; Lowe, Andrew (AMER CHEMICAL SOC, 2020)
The synthesis of the Rh(I)-aryl complex, Rh(I)(nbd)(BiPh)(P(4-FC6H4)3) is reported and its efficacy as an initiator for the (co)polymerization of phenylacetylenes established. The X-ray crystal structure indicates that the complex adopts a slightly distorted square planar geometry whose purity and structure was also confirmed by elemental analysis and 1H, 13C, 31P, 19F, 103Rh, and 31P-103Rh{1H} HMQC NMR spectroscopy. We demonstrate that Rh(I)(nbd)(BiPh)(P(4-FC6H4)3) mediates the (co)polymerization of phenylacetylenes in a controlled fashion with initiation efficiencies as high as 0.98, as evidenced by the pseudo-first-order kinetic and number-average molecular weight versus conversion profiles. The ability to form well-defined AB diblock copolymers, in a stereoregular manner, by sequential monomer addition is verified in the block copolymerization of phenylacetylene with 4-fluorophenylacetylene with quantitative crossover efficiency, as determined by size exclusion chromatography.